The outcomes of intravesical botox a injections in patients with refractory overactive bladder syndrome treated in GSH from 1 January 2016 to 31 December 2018 - Yaloko, Kibeni (Department of Obstetrics and Gynaecology, 2022)
Abstract Over the last 50 years botulinum toxin has become an effective medical therapy, used in a variety of specialities for different indications. A growing body of evidence indicates its beneficial effects in treating medication refractory detrusor over activity. This modality of treatment has been offered at Groote Schuur Hospital (GSH) in South Africa since 2012. Therefore, a review of our outcomes is necessary. Objective: Primary: 1. Determine the subjective success following intravesical Botox injections for the treatment of OABS. Secondary: 1. Describe the population of patients receiving intravesical Botox injections for the treatment of refractory OABS 2. Determine the rate and type of complications associated with intravesical Botox injection and the duration of treatment success. 3. Determine any patient factors associated with shorter duration of treatment success following the treatment of refractory OABS with intravesical Botox injections Methods: We conducted a quantitative, descriptive, retrospective study. The data collection sheet included the following details from the participants: demographic details, pre-existing medical conditions, method of diagnosis, and any previous treatment, the reason for stopping previous treatment, intra operative details and early complications at 1-6 weeks. Also included were details of any symptoms at follow up visits at 6- and 12-months post procedure. Subjective success was defined as the patients reporting improvement of symptoms at the first follow up visit. Duration of treatment success was defined as the time that lapsed between the date of Intravesical Botox injections and when the patient requested repeat treatment. Inclusion and exclusion criteria: We included patients who received intravesical Botox injections for OABS from 1 January 2016 - 31 December 2018. We excluded those who received intravesical Botox treatment for reasons other than OABS. Statistical analysis: A sample of 50 subjects was used. Summary statistics for age were reported as mean and standard deviation. Categorical variables were reported as simple frequencies and percentages. Associations between categorical variables were evaluated using the Fisher's exact test. Groups were compared in terms of age using the Tow-sample Mann-Whitney test. Analyses were performed using Stata Version 16. Results: The age of our participants ranged from 25 to 85 years (m = 54.72, ds = 14.74). 36% were post- menopausal, 92% were para 1 or more, 52% had a BMI of more than 30 kg/m2 , 30% were smokers, 40% were hypertensive and 10% had diabetes mellitus. All the patients reported improvement of symptoms at the 2-6 weeks' follow-up review. At the 6 months follow up visit less than a third of the participants complained of overactive bladder symptoms with only four (8%) patients requesting repeat intravesical Botox treatment. At the 12 months follow up visit just over half of the patients were experiencing overactive bladder symptoms with 21 (42%) requesting repeat intravesical Botox injections. There were few complications related to the intravesical Botox injection procedure. All the procedures were performed under local anaesthesia none of which needed to be abandoned due to pain of bleeding. Seven (14%) patients required temporary clean intermittent catheterisation (CIC). Eight (16%) patients had experienced a UTI (urinary tract infection) by the six weeks follow up visit. We found that hypertensive patients were significantly more likely to request repeat Botox at six months compared to non-hypertensive patients. Fisher's exact of 0,020. No other patient related factors showed any significant association in relation with repeat Botox injections at 6 months and 12 months. Conclusion: Our findings confirmed the benefit of intravesical Botox injection treatment in patients with OABS with minimal complications.